Developing an inclusive culture in the organization - D. S. Shikhalieva (Путеводитель предпринимателя, 2024)
The article discusses the features of an inclusive culture at two levels: the economy and the organization, and defines the concepts of «inclusive culture of an organization» and «inclusive leader». The author aims to analyze the main aspects related to the formation of an inclusive culture, which involves the development of the principles of equality and diversity. The work provides data confirming the need to introduce the principles of inclusiveness into the practice of Russian enterprises and organizations and presents conclusions about the impact of an inclusive culture on the effectiveness of the organization.